2007
DOI: 10.1002/ejoc.200700521
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosides with 5′‐Fixed Lipid Groups – Synthesis and Anchoring in Lipid Membranes

Abstract: Keywords: Nucleosides / Amphiphiles / Lipophilicity / Membrane anchoring / Synthesis Nucleosides were synthesized bearing one or two lipophilic groups at the 5Ј-position. The lipophilic substituents can be fixed at a 5Ј-amino group or at the 5Ј-phosphate moiety. Selected examples of these lipophilic nucleosides are shown by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…1 (20 mL). 1 13 A solution of 5Ј-DMT-protected 17 (0.44 g, 0.38 mmol) in dry CH 2 Cl 2 (80 mL) was stirred for 5 min. The organic layer was dried (MgSO 4 ), evaporated, and the residue was purified by column chromatography (cyclohexane/ EtOAc, 1:1) to give 13 (330 mg, 0.35 mmol, 77 %).…”
Section: ј-O-[13-bis(oleoyloxy)isopropyloxysuccinyl]uridine (11)mentioning
confidence: 99%
See 1 more Smart Citation
“…1 (20 mL). 1 13 A solution of 5Ј-DMT-protected 17 (0.44 g, 0.38 mmol) in dry CH 2 Cl 2 (80 mL) was stirred for 5 min. The organic layer was dried (MgSO 4 ), evaporated, and the residue was purified by column chromatography (cyclohexane/ EtOAc, 1:1) to give 13 (330 mg, 0.35 mmol, 77 %).…”
Section: ј-O-[13-bis(oleoyloxy)isopropyloxysuccinyl]uridine (11)mentioning
confidence: 99%
“…[1] Membrane passage of lipophilic nucleic acids was recently applied in siRNA-mediated in vivo gene therapy. [11] Recently we showed that nucleosides with lipid moieties connected either to the nucleobase [12] or to the 5Ј-position [13] anchor in the phospholipid double layers of giant and large unilamellar vesicles (GUV and LUV). [4][5][6] In all these cases the lipophilic moiety was attached either to the 5Ј-or 3Ј-OH group of the oligonucleotide by using the corresponding 3Ј-or 5Ј-lipidated nucleosides, respectively, as building blocks in the phosphoramidite method.…”
Section: Introductionmentioning
confidence: 99%
“…The Boc-protecting group was removed under standard conditions with trifluoroacetic acid in CH 2 Cl 2 , as described by Breipohl et al 42 Concurrently, the O-6 diphenylcarbamoyl protecting group was also cleaved under the acidic conditions; however, as the key intermediate 14 remained N-2-protected, the N-9 butylamino substituent could be functionalized with a decanoyl chain using DA and the coupling reagent O-(7-azabenzotriazol-1-yl)-N,N,N′,N′-tetramethyluronium hexafluoro-phosphate (HATU) to obtain 15. The final deprotection step, for which mild conditions (NH 3 in (11) was presynthesized coupled to 2-N-acetyl-6-O-DPC guanine (7). For the other routes, N-9-butylguanines with either an amino (14), carboxylic acid (17), or alkyne (18) handle were prepared, from which target molecules 4, 5, and 6 could be obtained in one or two steps.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In this case, investigation has been carried out with liposomes [10], micelles [11] and Langmuir monolayers of phospholipids [12,13]. For example, it has been shown that lipophilic nucleosides inserted into liposomes does not disturb considerably the lipid bilayer structure [14][15][16] and also that the nitrogen base interacts with the complementary bases of single-stranded DNA present in the aqueous phase [16,17].…”
Section: Introductionmentioning
confidence: 98%